Green Banking, Corporate Social Responsibility, and Firm Value: The Moderating Role of Non-Performing Loans - Ariyanto Bakti Pangala; Rousilita Suhendah (Golden Ratio of Finance Management, 2026)
This study examines whether green banking and corporate social responsibility (CSR) affect firm value and whether non-performing loans (NPLs) moderate these relationships. The study uses publicly available audited financial statements, annual reports, and sustainability reports of banking companies listed on the Indonesia Stock Exchange for the 2022–2024 period. Purposive sampling identified 24 eligible banks and 72 initial firm-year observations; after nine outlier observations were excluded, the final balanced panel comprised 21 banks and 63 observations. Green banking was measured using a green banking disclosure index, corporate social responsibility was measured using a CSR disclosure index, firm value was measured using Tobin's Q, and non-performing loans were measured using the NPL ratio. Panel-data moderated regression was estimated in EViews 12. The Chow, Hausman, and Lagrange Multiplier tests supported the random effects model. Green banking (β = -1.0361; p = 0.1126) and CSR (β = 0.0176; p = 0.9612) had no significant direct effect on firm value. The green banking-NPL interaction was positive and significant (β = 66.6937; p = 0.0056), while the CSR-NPL interaction was not significant (β = -11.0913; p = 0.4143). These findings indicate that credit-risk conditions change the market relevance of green banking disclosure and underscore the need to integrate sustainability disclosure with disciplined credit-risk management.